BCL-XL as a tumour prognostic factor? - Kaczmarek-Borowska, Bożenna; Zmorzyński, Szymon; Filip, Agata; Wojcierowski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2010)
BCL-2 family proteins are key regulators of programmed cell death or apoptosis, which is implicated in many human diseases, particularly cancer. The BCL-2 family includes both anti- and pro-apoptotic proteins with opposing biological functions in either inhibiting or promoting cell death. High expression of anti-apoptotic members such as BCL-XL commonly found in human cancer contributes to neoplastic cell expansion and interferes with the therapeutic action of many chemotherapeutic drugs. The functional blockade of BCL-XL could either restore the apoptotic process in tumour cells or sensitize these tumours for chemo- and radiotherapies. Increased expression of BCL-XL protein has been reported in many tumours: breast cancer, lung cancer, prostate cancer, pancreatic cancer, colon cancer, ovarian cancer and in lymphomas, leukaemias, melanomas and head and neck cancers. The results show that BCL-XL overexpression may be a poor prognostic factor in non-small cell lung cancer and colon cancer, which means bad prognosis and resistance to chemotherapy.